Effect of high temperature on the microstructural evolution of fiber reinforced geopolymer composite - Samal, Sneha (Heliyon, 2019)
Physical evolution of geopolymeric minerals derived from metakaolin and synthesized with sodium, mixed-alkali and potassium activating solutions (Na- K) during thermal exposure. The geopolymer composites were prepared with 40 V% of fiber reinforcement such as carbon, E-glass, and basalt at the direction of in plain. Fiber reinforced geopolymer composites were exposed to the room and elevated temperatures inside the oven at air medium for a period of 30 min. The durability of the composites and internal structures with surface microstructures were examined after high temperature exposures. According to the results, geopolymer implied a prominent influence on the thermal shrinkage with the increasing of Si/Al ratios. This was attributed to the densification caused by reduction in porosity during dehydroxylation and sintering. In the case of carbon fiber reinforced composite shows transition in strength after 600 °C due to the oxide protective layer that increases the flexural strength and toughness of the composite. The flexural strength of the carbon reinforced composite increases from 17.8 to 55.8 MPa at 1000 °C. Whereas, E-glass reinforced composite shows expansion in a matrix with cage like structure helps in the sliding mechanism of fiber within the matrix, thus strength reduces towards high temperature. In case of basalt reinforces composite complete conversions into a ceramic like structure after exposure to high temperature. As a result, the crystalline nature of ceramic assists in toughened the composite structure with a brittle nature.
Keywords: Structural engineering; Mechanical engineering; Civil engineering; Materials science